Antiretroviral treatment of HIV-2 infection. (August 2017) - Mendoza, Carmen de; Requena, Silvia; Caballero, Estrella; Cabezas, Teresa; Peñaranda, María; Amengual, María José; Sáez, Ana; Lozano, Ana Belén; Ramos, José M; Soriano, Vincent
HIV-2 is a neglected virus despite estimates of 1–2 million people being infected worldwide. AIDS develops more slowly in HIV-2 than HIV-1. Outside endemic regions, HIV-2 is mostly found in immigrants from west Africa or their sex partners. There are four major caveats when treating HIV-2. First, some antiretrovirals are not or only partially active against HIV-2. Second, CD4 declines in HIV-2 occur slowly, but CD4 recovery is smaller with antiretroviral treatment. Third, both virological failure and rapid emergence of drug resistance occur more frequently in HIV-2 than HIV-1. Finally, misdiagnosis of HIV-2 in patients wrongly considered as infected with HIV-1 or in those dually infected may result in treatment failures with undetectable HIV-1 RNA. Integrase inhibitors, and especially dolutegravir, should be part of any preferred HIV-2 antiretroviral combination nowadays.